Solid-state electrolyte and solid-state battery comprising same
By adding conductive salts and nitrogen-containing aromatic copolymers to the inorganic solid electrolyte, and performing hot pressing molding and low-temperature plasma treatment, the problem of large interface impedance of the inorganic solid electrolyte is solved, the cycle life and ionic conductivity of the battery are improved, and the cycle life and ionic conductivity of the battery are achieved. High-performance solid electrolytes.
Patent Information
- Application Number
- CN202411424058.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
AI Technical Summary
Inorganic solid electrolytes have problems such as large interface impedance, brittleness and poor mechanical properties in all-solid lithium batteries, which affect their application performance.
Add an appropriate amount of conductive salt and nitrogen-containing aromatic copolymer to the traditional inorganic solid electrolyte, and form a highly elastic solid electrolyte through hot pressing molding and low-temperature plasma treatment, reducing interface impedance and improving conductivity.
The high compatibility of solid electrolytes and electrode materials is achieved, which extends the cycle life of the battery and improves ionic conductivity and mechanical properties.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a solid electrolyte and a solid battery comprising the electrolyte. Background Art
[0002] Compared with traditional lithium-ion batteries that use electrolytes, all-solid-state lithium batteries use solid electrolytes instead of electrolytes and separators, which can effectively avoid thermal runaway problems caused by leakage, extrusion, and puncture, and improve battery safety. Therefore, all-solid-state lithium batteries have attracted great attention in the field of new energy vehicles.
[0003] The preparation of solid electrolytes is one of the key technologies of all-solid-state lithium-ion batteries, and predecessors have made a lot of research on this. For example, the patent with application number 2019102099847 discloses an all-solid-state composite polymer solid electrolyte and its preparation method. The solid electrolyte matrix used is a blend of polyethylene oxide and polyperfluorohexylethyl methacrylate, which has the characteristics of wide electrochemical window, high ionic conductivity, stable performance and good mechanical properties. However, this patent requires the use of polyperfluorohexylethyl methacrylate as the matrix material, and its preparation process is relatively complicated and costly, which is not suitable for large-scale production.
[0004] Inorganic solid electrolytes have shown many advantages in all-solid-state lithium batteries due to their high electrical conductivity, such as their ability to adapt to high-voltage positive electrodes. However, inorganic solid electrolytes are hard and brittle, and their interface impedance with electrodes is large. How to reduce the interface resistance of inorganic solid electrolytes has become an urgent problem to be solved in this field. Summary of the invention
[0005] In order to reduce the interfacial impedance of an inorganic solid electrolyte, the present invention provides a solid electrolyte and a solid-state battery including the electrolyte. The present invention adds a conductive salt and a nitrogen-containing aromatic copolymer, especially LATP, in a conventional inorganic solid electrolyte in appropriate weight portions, so as to avoid the generation of lithium dendrites inside the electrolyte. The nitrogen-containing aromatic copolymer is obtained by copolymerizing a first polymer and a second polymer. The first polymer is selected from aromatic polyamide, and the second polymer is selected from polyvinyl alcohol, polyethylene oxide, poly(N-vinyl carbazole), polyvinyl pyrrolidone, poly(2-vinyl pyridine), poly(4-vinyl pyridine), and polyacrylonitrile. By introducing the functional groups of the above aromatic structures, the anions in the lithium salt form covalent bonds with the polymer network to fix the anions, thereby realizing pure lithium ion conduction. At the same time, the interaction force between the nitrogen-containing aromatic copolymer and the lithium ions is weak, which helps the migration of lithium ions therein, thereby improving the ionic conductivity. The nitrogen-containing aromatic copolymer is obtained by copolymerizing the first polymer and the second polymer, and can have a better hot pressing molding effect with the inorganic solid electrolyte, effectively improving the elasticity of the solid electrolyte product, so that the product has the advantages of high ionic conductivity and long cycle life.
[0006] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a solid electrolyte comprising the following components in parts by weight: 20 to 60 parts of an inorganic solid electrolyte, 1 to 40 parts of a conductive salt, and 0.5 to 45 parts of a nitrogen-containing aromatic copolymer; in: The inorganic solid electrolyte is selected from at least one of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphide, lithium lanthanum titanium oxide and lithium aluminum germanium phosphide; The nitrogen-containing aromatic copolymer is obtained by copolymerizing a first polymer and a second polymer, wherein the first polymer is selected from aromatic polyamide, and the second polymer is selected from at least one of polyvinyl alcohol, polyethylene oxide, poly(N-vinyl carbazole), polyvinyl pyrrolidone, poly(2-vinyl pyridine), poly(4-vinyl pyridine), and polyacrylonitrile.
[0007] Traditional inorganic solid electrolytes have the problem of large contact impedance with electrodes. The present invention increases the interfacial compatibility between solid electrolyte products and electrode materials by adding appropriate weight portions of conductive salts and nitrogen-containing aromatic copolymers to traditional inorganic solid electrolytes. The addition of nitrogen-containing aromatic copolymers gives the solid electrolyte of the present invention elasticity, thereby avoiding the interfacial mismatch problem caused by the volume change of electrode active materials during the use of the battery. Therefore, the battery prepared by the solid electrolyte provided by the present invention has excellent performance of high ion conductivity and long cycle life.
[0008] In the solid electrolyte of the present invention, one of the key points is that, based on 20 to 60 parts of inorganic solid electrolyte, the mass of the added conductive salt and nitrogen-containing aromatic copolymer needs to be 1 to 40 parts of conductive salt and 0.5 to 45 parts of nitrogen-containing aromatic copolymer. Wherein, the inorganic solid electrolyte is selected from lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate, lithium lanthanum titanium oxide and lithium aluminum germanium phosphate. Adding appropriate weight parts of conductive salt and nitrogen-containing aromatic copolymer, especially LATP, to the above-mentioned traditional inorganic solid electrolyte can avoid the formation of lithium dendrites inside. The nitrogen-containing aromatic copolymer is obtained by copolymerization of a first polymer and a second polymer, the first polymer is selected from aromatic polyamide, and the second polymer is selected from polyvinyl alcohol, polyethylene oxide, poly(N-vinyl carbazole), polyvinyl pyrrolidone, poly(2-vinyl pyridine), poly(4-vinyl pyridine), and polyacrylonitrile. By introducing the functional groups of the above-mentioned aromatic structure, the anions in the lithium salt form covalent bonds with the polymer network, fix the anions, and thus achieve pure lithium ion conduction. At the same time, the interaction between the nitrogen-containing aromatic copolymer and lithium ions is weak, which helps the migration of lithium ions therein, thereby improving ionic conductivity. The nitrogen-containing aromatic copolymer is obtained by copolymerization of the first polymer and the second polymer, and can have a better hot pressing molding effect with the inorganic solid electrolyte, effectively improving the elasticity of the solid electrolyte product, so that the product has the advantages of high ionic conductivity and long cycle life.
[0009] As a preferred solid electrolyte, the aromatic polyamide is selected from at least one of poly(p-phenylene terephthalamide) and poly(m-phenylene isophthalamide).
[0010] As a preferred embodiment of the solid electrolyte, the mass ratio of the first polymer to the second polymer is 2 to 7:1.
[0011] As a preferred solid electrolyte, the conductive salt is selected from at least one of LiTFSI, LiClO4 and LiPF6.
[0012] Further preferably, the conductive salt is LiTFSI. When the conductive salt is LiTFSI, it is mixed with the traditional inorganic solid electrolyte LATP and the nitrogen-containing aromatic copolymer, hot-pressed, and treated with low-temperature plasma. Compared with other conductive salts, it has higher ionic conductivity and better cycle life. However, other conductive salts are mixed with traditional inorganic solid electrolytes LATP and nitrogen-containing aromatic copolymers, hot-pressed, and treated with low-temperature plasma, and their ionic conductivity and cycle life are not significantly improved. It can be seen that low-temperature plasma treatment enables LiTFSI to play a role in solid electrolyte products.
[0013] In a second aspect, the present invention provides a method for preparing the solid electrolyte as described above, comprising the following steps: (1) mixing an inorganic solid electrolyte, a conductive salt, and a nitrogen-containing aromatic copolymer uniformly and hot pressing them into a mold; (2) subjecting the formed solid electrolyte to low-temperature plasma treatment, wherein the gas used for the low-temperature plasma treatment is a mixed gas of oxygen, ammonia, and nitrogen; (3) Cleaning the solid electrolyte after low-temperature plasma treatment.
[0014] With respect to the solid electrolyte provided by the present invention, the present invention also provides a preparation method comprising the above steps (1) to (3). In the preparation method, an inorganic solid electrolyte, a conductive salt, and a nitrogen-containing aromatic copolymer are uniformly mixed, hot-pressed, and then placed in a low-temperature plasma treatment machine. The solid electrolyte is treated with plasma gas and doped with oxygen and nitrogen elements, which can make it more difficult for the solid electrolyte to generate dendrites and extend the cycle life. At the same time, the surface of the solid electrolyte is modified with oxygen, ammonia, and nitrogen ions, which can improve the compatibility of the solid electrolyte with the electrode material and reduce the interface impedance.
[0015] As a preferred embodiment of the above preparation method, the temperature of hot pressing is 60-130°C.
[0016] As a preferred embodiment of the above preparation method, the volume ratio of oxygen, ammonia and nitrogen is 3 to 5:1 to 4:2.
[0017] In a third aspect, the present invention provides the use of the above-mentioned solid electrolyte in the preparation of an all-solid-state battery.
[0018] In a fourth aspect, the present invention provides a solid electrolyte membrane prepared using the above-mentioned solid electrolyte.
[0019] In a fifth aspect, the present invention provides an all-solid-state battery comprising the above-mentioned solid-state electrolyte.
[0020] Compared with the prior art, the present invention has the following technical effects: (1) The solid electrolyte provided by the present invention increases the interfacial compatibility between the solid electrolyte product and the electrode material by adding appropriate weight portions of conductive salt and nitrogen-containing aromatic copolymer to the traditional inorganic solid electrolyte. The addition of the nitrogen-containing aromatic copolymer gives the solid electrolyte of the present invention elasticity, thereby avoiding the interfacial mismatch problem caused by the volume change of the electrode active material during the use of the battery. Therefore, the battery prepared by the solid electrolyte provided by the present invention has excellent performance of high ion conductivity and long cycle life.
[0021] (2) The present invention provides a preparation method, wherein an inorganic solid electrolyte, a conductive salt, and a nitrogen-containing aromatic copolymer are uniformly mixed, hot-pressed, and then placed in a low-temperature plasma treatment machine, and the solid electrolyte is treated with plasma gas to dope oxygen and nitrogen elements, which can make it more difficult for the solid electrolyte to generate dendrites and extend the cycle life. At the same time, the surface of the solid electrolyte is modified with oxygen, ammonia, and nitrogen ions, which can improve the compatibility of the solid electrolyte with the electrode material and reduce the interface impedance. DETAILED DESCRIPTION
[0022] The present invention provides a solid electrolyte, comprising the following components in parts by weight: 20 to 60 parts of an inorganic solid electrolyte, 1 to 40 parts of a conductive salt, and 0.5 to 45 parts of a nitrogen-containing aromatic copolymer; in: The inorganic solid electrolyte is selected from at least one of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphide, lithium lanthanum titanium oxide and lithium aluminum germanium phosphide; The nitrogen-containing aromatic copolymer is obtained by copolymerizing a first polymer and a second polymer, wherein the first polymer is selected from aromatic polyamide, and the second polymer is selected from at least one of polyvinyl alcohol, polyethylene oxide, poly(N-vinyl carbazole), polyvinyl pyrrolidone, poly(2-vinyl pyridine), poly(4-vinyl pyridine), and polyacrylonitrile.
[0023] Traditional inorganic solid electrolytes have the problem of large contact impedance with electrodes. The present invention increases the interfacial compatibility between solid electrolyte products and electrode materials by adding appropriate weight portions of conductive salts and nitrogen-containing aromatic copolymers to traditional inorganic solid electrolytes. The addition of nitrogen-containing aromatic copolymers gives the solid electrolyte of the present invention elasticity, thereby avoiding the interfacial mismatch problem caused by the volume change of electrode active materials during the use of the battery. Therefore, the battery prepared by the solid electrolyte provided by the present invention has excellent performance of high ion conductivity and long cycle life.
[0024] In the solid electrolyte of the present invention, one of the key points is that, based on 20 to 60 parts of inorganic solid electrolyte, the mass of the added conductive salt and nitrogen-containing aromatic copolymer needs to be 1 to 40 parts of conductive salt and 0.5 to 45 parts of nitrogen-containing aromatic copolymer. Wherein, the inorganic solid electrolyte is selected from lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate, lithium lanthanum titanium oxide and lithium aluminum germanium phosphate. Adding appropriate weight parts of conductive salt and nitrogen-containing aromatic copolymer, especially LATP, to the above-mentioned traditional inorganic solid electrolyte can avoid the formation of lithium dendrites inside. The nitrogen-containing aromatic copolymer is obtained by copolymerization of a first polymer and a second polymer, the first polymer is selected from aromatic polyamide, and the second polymer is selected from polyvinyl alcohol, polyethylene oxide, poly(N-vinyl carbazole), polyvinyl pyrrolidone, poly(2-vinyl pyridine), poly(4-vinyl pyridine), and polyacrylonitrile. By introducing the functional groups of the above-mentioned aromatic structure, the anions in the lithium salt form covalent bonds with the polymer network, fix the anions, and thus achieve pure lithium ion conduction. At the same time, the interaction between the nitrogen-containing aromatic copolymer and lithium ions is weak, which helps the migration of lithium ions therein, thereby improving the ionic conductivity. The nitrogen-containing aromatic copolymer is obtained by copolymerization of the first polymer and the second polymer, and can have a better hot pressing molding effect with the inorganic solid electrolyte, effectively improve the elasticity and self-healing ability of the solid electrolyte product, avoid interface mismatch, and thus make the product have the advantages of high ionic conductivity and long cycle life.
[0025] As a preferred solid electrolyte, the aromatic polyamide is selected from at least one of poly(p-phenylene terephthalamide) and poly(m-phenylene isophthalamide).
[0026] As a preferred embodiment of the solid electrolyte, the mass ratio of the first polymer to the second polymer is 2 to 7:1.
[0027] As a preferred solid electrolyte, the conductive salt is selected from at least one of LiTFSI, LiClO4 and LiPF6.
[0028] With respect to the above-mentioned solid electrolyte provided by the present invention, the present invention also provides a preparation method, comprising the following steps: (1) Mix 20 to 60 parts of an inorganic solid electrolyte, 1 to 40 parts of a conductive salt, and 0.5 to 45 parts of a nitrogen-containing aromatic copolymer uniformly by weight, and perform hot pressing molding; (2) subjecting the formed solid electrolyte to low-temperature plasma treatment, wherein the gas used for the low-temperature plasma treatment is a mixed gas of oxygen, ammonia, and nitrogen; (3) Cleaning the solid electrolyte after low-temperature plasma treatment.
[0029] The preparation method is to mix the inorganic solid electrolyte, conductive salt and nitrogen-containing aromatic copolymer evenly, and then put them into a low-temperature plasma treatment machine after hot pressing. The solid electrolyte is treated with plasma gas and doped with oxygen and nitrogen elements, which can make it more difficult for the solid electrolyte to generate dendrites and extend the cycle life. At the same time, the surface of the solid electrolyte is modified with oxygen, ammonia and nitrogen ions, which can improve the compatibility of the solid electrolyte with the electrode material and reduce the interface impedance.
[0030] In one embodiment, when the conductive salt is LiTFSI, it is mixed with a traditional inorganic solid electrolyte LATP and a nitrogen-containing aromatic copolymer, hot-pressed, and treated with low-temperature plasma. Compared with other conductive salts, it has higher ionic conductivity and better cycle life. However, other conductive salts are mixed with traditional inorganic solid electrolytes LATP and nitrogen-containing aromatic copolymers, hot-pressed, and treated with low-temperature plasma, and their ionic conductivity and cycle life are not significantly improved. It can be seen that low-temperature plasma treatment enables LiTFSI to play a role in solid electrolyte products.
[0031] As a preferred embodiment of the above preparation method, the temperature of hot pressing is 60-130°C.
[0032] As a preferred embodiment of the above preparation method, the volume ratio of oxygen, ammonia and nitrogen is 3 to 5:1 to 4:2.
[0033] The present invention will be further described below in conjunction with embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should belong to the scope of protection of the present invention.
[0034] Example 1 A solid electrolyte is provided, which is prepared according to the following steps: (1) By weight, 40 parts of LATP, 21 parts of conductive salt LiTFSI, and 30 parts of nitrogen-containing aromatic copolymer are mixed uniformly and hot-pressed at 80° C. The nitrogen-containing aromatic copolymer is obtained by copolymerizing poly(p-phenylene terephthalamide) and poly(N-vinyl carbazole) in a mass ratio of 4:1.
[0035] (2) The formed solid electrolyte is placed in a low-temperature plasma treatment machine, and a mixed gas of oxygen, ammonia, and nitrogen is introduced at a volume ratio of 4:3:2 for low-temperature plasma treatment. The treatment time is 10 minutes and the treatment pressure is 40 MPa.
[0036] (3) Clean the solid electrolyte after low-temperature plasma treatment with deionized water.
[0037] Example 2 A solid electrolyte is provided, which is prepared according to the following steps: (1) By weight, 60 parts of LATP, 40 parts of conductive salt LiTFSI, and 45 parts of nitrogen-containing aromatic copolymer are mixed evenly and hot-pressed at 60° C. The nitrogen-containing aromatic copolymer is obtained by copolymerizing poly(p-phenylene terephthalamide) and polyethylene oxide in a mass ratio of 2:1.
[0038] (2) The formed solid electrolyte is placed in a low-temperature plasma treatment machine, and a mixed gas of oxygen, ammonia, and nitrogen is introduced at a volume ratio of 3:1:2 for low-temperature plasma treatment. The treatment time is 10 minutes and the treatment pressure is 40 MPa.
[0039] (3) Clean the solid electrolyte after low-temperature plasma treatment with deionized water.
[0040] Example 3 A solid electrolyte is provided, which is prepared according to the following steps: (1) According to weight, 20 parts of LATP, 1 part of conductive salt LiTFSI, and 10 parts of nitrogen-containing aromatic copolymer are mixed evenly and hot-pressed at 80° C. The nitrogen-containing aromatic copolymer is obtained by copolymerizing poly(p-phenylene terephthalamide) and poly(vinyl pyrrolidone) in a mass ratio of 7:1.
[0041] (2) The formed solid electrolyte is placed in a low-temperature plasma treatment machine, and a mixed gas of oxygen, ammonia, and nitrogen is introduced at a volume ratio of 4:3:2 for low-temperature plasma treatment. The treatment time is 10 minutes and the treatment pressure is 40 MPa.
[0042] (3) Clean the solid electrolyte after low-temperature plasma treatment with deionized water.
[0043] Example 4 A solid electrolyte is provided, and the preparation thereof is different from that of Example 1, except that 21 parts of LiTFSI are replaced by 21 parts of LiClO4. The rest is the same as that of Example 1.
[0044] Example 5 A solid electrolyte is provided, and the preparation thereof is different from that of Example 1, except that 21 parts of LiTFSI are replaced by 21 parts of LiPF6. The rest is the same as that of Example 1.
[0045] Example 6 A solid electrolyte is provided, and the preparation method thereof is the same as that of Example 1, except that poly(N-vinyl carbazole) is replaced by polyvinyl alcohol. The other steps are the same as those of Example 1.
[0046] Example 7 A solid electrolyte is provided, and the preparation method thereof is different from that of Example 1, except that poly(N-vinylcarbazole) is replaced by polyvinyl pyrrolidone. The rest is the same as that of Example 1.
[0047] Example 8 A solid electrolyte is provided, and the preparation method thereof is the same as that of Example 1, except that poly(2-vinylpyridine) is added instead of poly(N-vinylcarbazole). The other preparation methods are the same as those of Example 1.
[0048] Example 9 A solid electrolyte is provided, and the preparation method thereof is the same as that of Example 1, except that poly(4-vinylpyridine) is added instead of poly(N-vinylcarbazole). Other preparation methods are the same as those of Example 1.
[0049] Example 10 A solid electrolyte is provided, and the preparation method thereof is the same as that of Example 1, except that poly(N-vinylcarbazole) is replaced by polyacrylonitrile. Other steps are the same as those of Example 1.
[0050] Comparative Example 1 A solid electrolyte is provided, and the preparation thereof is different from that of Example 1 except that the low-temperature plasma treatment in step (2) is not performed. Other aspects are the same as those of Example 1.
[0051] Comparative Example 2 A solid electrolyte is provided, and its preparation is different from that of Example 1, except that in step (2), a mixed gas of oxygen, ammonia and nitrogen is introduced at a volume ratio of 4:1:2 for low-temperature plasma treatment. The rest is the same as that of Example 1.
[0052] Comparative Example 3 A solid electrolyte is provided, and its preparation is different from that of Example 1, except that in step (2), a mixed gas of oxygen, ammonia and nitrogen is introduced at a volume ratio of 4:9:2 for low-temperature plasma treatment. The rest is the same as that of Example 1.
[0053] Comparative Example 4 A solid electrolyte is provided, and its preparation is different from that of Example 1, except that in step (2), a mixed gas of oxygen, ammonia and nitrogen is introduced at a volume ratio of 2:3:2 for low-temperature plasma treatment. The rest is the same as that of Example 1.
[0054] Comparative Example 5 A solid electrolyte is provided, and its preparation is different from that of Example 1, except that in step (2), a mixed gas of oxygen, ammonia and nitrogen is introduced at a volume ratio of 7:3:2 for low-temperature plasma treatment. Other aspects are the same as those of Example 1.
[0055] Comparative Example 6 A solid electrolyte is provided, and its preparation is different from that of Example 2 except that the low-temperature plasma treatment in step (2) is not performed. Other aspects are the same as those of Example 1.
[0056] Comparative Example 7 A solid electrolyte is provided, and its preparation is different from that of Example 3 except that the low-temperature plasma treatment in step (2) is not performed. Other aspects are the same as those of Example 1.
[0057] Comparative Example 8 A solid electrolyte is provided, and the preparation method thereof is different from that of Example 1 except that no poly(N-vinylcarbazole) is added.
[0058] This comparative example was prepared according to the following steps: (1) By weight, 40 parts of LATP, 21 parts of conductive salt LiTFSI, and 30 parts of poly(p-phenylene terephthalamide) were mixed evenly and hot-pressed at 80°C.
[0059] (2) The formed solid electrolyte is placed in a low-temperature plasma treatment machine, and a mixed gas of oxygen, ammonia, and nitrogen is introduced at a volume ratio of 4:3:2 for low-temperature plasma treatment. The treatment time is 10 minutes and the treatment pressure is 40 MPa.
[0060] (3) Clean the solid electrolyte after low-temperature plasma treatment with deionized water.
[0061] Performance Testing The solid electrolyte obtained in the embodiment and the comparative example was tested for room temperature ionic conductivity, and button-type solid-state lithium batteries were assembled for AC impedance test and cycle test. The results are shown in Table 1. The assembly method of the solid-state lithium battery is as follows: the positive electrode active material NCM811, the adhesive PVDF, and the conductive agent LITX300 are mixed in a mass ratio of 90:5:5, NMP is added, and a uniform positive electrode slurry is obtained by stirring under the action of a vacuum mixer, and then evenly coated on the surface of the aluminum current collector, dried, and cut to obtain a positive electrode; the lithium metal foil is rolled and attached to the surface of the copper current collector, and the negative electrode is cut to obtain a negative electrode; the positive electrode and the negative electrode are respectively placed on both sides of the solid electrolyte for assembly and packaging to obtain an all-solid-state lithium battery. The room temperature ionic conductivity test method is as follows: the solid electrolyte membrane is punched into a disc, assembled with stainless steel into a counter electrode, the frequency range is 106~1Hz, the amplitude is 10Mv, and the ionic conductivity of the sample is tested. The AC impedance test method is: using a chemical workstation for testing, parameter settings: amplitude 10mV, frequency range 0.1Hz~4MHz. The cycle test method is: at room temperature, 0.3C charging, 0.3C discharging, charge and discharge range 2.8~4.25V, cycle test, and determine the number of cycles required to reach 80% of the initial capacity.
[0062] Table 1 Group <![CDATA[Ionic conductivity / (10 -4 S·cm -1 )]]> Impedance / mΩ Required number of cycles Example 1 11.7 31 832 Example 2 9.21 42 671 Example 3 9.33 40 668 Example 4 9.70 47 614 Example 5 9.52 46 653 Example 6 8.02 58 599 Example 7 8.11 61 590 Example 8 8.07 72 532 Example 9 8.16 69 549 Example 10 8.27 70 542 Comparative Example 1 9.45 43 669 Comparative Example 2 9.50 47 662 Comparative Example 3 9.45 49 657 Comparative Example 4 9.51 50 648 Comparative Example 5 9.49 48 654 Comparative Example 6 9.21 44 682 Comparative Example 7 9.33 47 678 Comparative Example 8 7.63 82 501 From Table 1, we can see that: The present invention increases the interfacial compatibility between the solid electrolyte product and the electrode material by adding appropriate weight portions of conductive salt and nitrogen-containing aromatic copolymer to the traditional inorganic solid electrolyte. The addition of the nitrogen-containing aromatic copolymer gives the solid electrolyte of the present invention elasticity, thereby avoiding the interfacial mismatch problem of the solid electrolyte caused by the volume change of the electrode active material during the use of the battery, so that the obtained battery has the excellent performance of low interfacial impedance and long cycle life, and the inorganic solid electrolyte can maintain the performance of high ion conductivity.
[0063] By comparing Comparative Example 1 with Example 1, it can be seen that by treating the solid electrolyte with plasma gas and doping oxygen and nitrogen elements, the solid electrolyte can be made more difficult to generate dendrites and extend the cycle life; at the same time, the surface of the solid electrolyte is modified with oxygen, ammonia and nitrogen ions, which can improve the compatibility of the solid electrolyte with the electrode material and reduce the interface impedance. It can be seen from the analysis of Examples 1 to 3, Comparative Example 1, and Comparative Examples 5-6 that when the conductive salt is LiTFSI, it is mixed with traditional inorganic solid electrolytes LATP and nitrogen-containing aromatic copolymers, hot-pressed, and treated with low-temperature plasma. Compared with other conductive salts, the interface impedance is lower and the cycle life is better. Other conductive salts, such as LiClO4 and LiPF6, are mixed with traditional inorganic solid electrolytes LATP and nitrogen-containing aromatic copolymers, hot-pressed, and treated with low-temperature plasma. After being treated with low-temperature plasma, their cycle life is not significantly improved. It can be seen that low-temperature plasma treatment enables LiTFSI to play a role in solid electrolyte products.
[0064] The influence of low-temperature plasma treatment parameters on the performance of solid electrolytes and all-solid-state batteries prepared therefrom can be shown by comparing comparative examples 2 to 4 with example 1. It can be seen that when the solid electrolyte is treated with plasma gas, the volume ratio of oxygen, ammonia and nitrogen needs to be 3 to 5:1 to 4:2.
[0065] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0066] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A solid electrolyte, characterized in that: The composition comprises the following components in parts by weight: 20-60 parts of inorganic solid electrolyte, 1-40 parts of conductive salt, 0.5-45 parts of nitrogen-containing aromatic copolymer; in: The inorganic solid electrolyte is selected from at least one of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphide, lithium lanthanum titanium oxide and lithium aluminum germanium phosphide; The nitrogen-containing aromatic copolymer is obtained by copolymerizing a first polymer and a second polymer, wherein the first polymer is selected from aromatic polyamide, and the second polymer is selected from at least one of polyvinyl alcohol, polyethylene oxide, poly(N-vinyl carbazole), polyvinyl pyrrolidone, poly(2-vinyl pyridine), poly(4-vinyl pyridine), and polyacrylonitrile.
2. A solid electrolyte according to claim 1, characterized in that: The aromatic polyamide is selected from at least one of poly(p-phenylene terephthalamide) and poly(m-phenylene isophthalamide).
3. A solid electrolyte according to claim 1 or 2, characterized in that: The mass ratio of the first polymer to the second polymer is 2 to 7:
1.
4. A solid electrolyte according to claim 1, characterized in that: The conductive salt is selected from at least one of LiTFSI, LiClO4 and LiPF6.
5. The method for preparing a solid electrolyte according to claim 1, wherein: The following steps are involved: (1) mixing an inorganic solid electrolyte, a conductive salt, and a nitrogen-containing aromatic copolymer uniformly and hot pressing them into a mold; (2) subjecting the formed solid electrolyte to low-temperature plasma treatment, wherein the gas used for the low-temperature plasma treatment is a mixed gas of oxygen, ammonia, and nitrogen; (3) Cleaning the solid electrolyte after low-temperature plasma treatment.
6. The preparation method according to claim 5, characterized in that: The temperature of hot pressing is 60-130°C.
7. The preparation method according to claim 5, characterized in that: The volume ratio of oxygen, ammonia and nitrogen is 3-5:1-4:
2.
8. Use of the solid electrolyte according to any one of claims 1 to 4 in the preparation of an all-solid-state battery.
9. A solid electrolyte membrane, characterized in that: It is prepared by using the solid electrolyte described in any one of claims 1 to 4.
10. An all-solid-state battery, characterized in that: It comprises the solid electrolyte according to any one of claims 1 to 4.
Citation Information
Patent Citations
Method for modifying garnet type composite solid electrolyte by plasma interface
CN112331907A
Solid electrolyte and lithium ion battery including same
CN117121249A
Solid-state battery cathodes and methods thereof
US20230026596A1
